2021
DOI: 10.1063/5.0047379
|View full text |Cite
|
Sign up to set email alerts
|

Vortex dynamics and fractal structures in reactive and nonreactive Richtmyer–Meshkov instability

Abstract: Hydrodynamic instabilities caused by shock-flame interactions are a fundamental challenge in the accurate prediction of explosion loads in the context of nuclear and process plant safety. To investigate the Richtmyer-Meshkov instability (RMI), a series of three dimensional numerical simulations of shock-flame interactions is performed, including lean, stoichiometric and nonreactive homogeneous H 2 /Air mixtures. The equivalence ratio has a strong influence on the achievable flame wrinkling and mixing, by impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…2015; Bambauer et al. 2020, 2021). The regulations should be extended to some practical applications, and we carry out three-dimensional DNS with multi-mode perturbations and a detailed chemical mechanism of the cylindrical geometry in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; Bambauer et al. 2020, 2021). The regulations should be extended to some practical applications, and we carry out three-dimensional DNS with multi-mode perturbations and a detailed chemical mechanism of the cylindrical geometry in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Bambauer et al. (2021) investigated the vortex dynamics and fractal structures in reactive RMI, and confirmed that baroclinic torque is dominant during shock-flame interactions. The interactions of the incident shock wave and combustion waves would result in non-planarity effects from combined RTI and RMI actions (Attal & Ramaprabhu 2015; Zhou 2017 a ).…”
Section: Introductionmentioning
confidence: 91%
“…Choosing the channel cross-section for normalization , the normalized flame surface area can be interpreted as a wrinkling factor, which is of a pivotal importance for the closure of the reactive source term in under-resolved simulation approaches. The development of the normalized flame surface area can be described in two phases 18 . The first phase, following the initial shock flame interaction, is dominated by the effects of flame thickness, where the thinner stoichiometric flame is more susceptible to flame wrinkling than the thicker lean flame.…”
Section: Resultsmentioning
confidence: 99%
“…High-fidelity simulation data of shock-flame interactions of a planar shock wave interacting with a statistically planar /air flame in a rectangular channel is used to study the temporal development and topology of flame self interactions (FSI) occurring due to RMI. The equivalence ratio is found to be a major influencing factor on the FSI as it affects the flame thickness and reactivity 17 , 18 . At early stages of the RMI, after the first shock flame interaction, a slight increase in FSI can be detected for the stoichiometric case ( ), as its relatively thinner flame front allows for a higher amount of flame distortion compared to the lean ( ) case.…”
Section: Discussionmentioning
confidence: 99%
“…This enthusiastic response is another indication of the respect Ted O'Brien has within the international research community of turbulence and reactive flows. These contributions are on diverse topics including combustion instability, 150,151 scalar mixing, [152][153][154][155][156] homogeneous isotropic turbulence, [157][158][159][160] turbulent premixed flames, [161][162][163][164][165][166][167][168][169][170][171] turbulent non-premixed flames, [172][173][174][175] wallbounded turbulence, [176][177][178] turbulent combustion modeling, [179][180][181] FDF/PDF, [182][183][184][185][186][187][188][189][190][191][192] and two-phase turbulent flows. [193][194][195][196]<...…”
Section: Organization Of This Simentioning
confidence: 99%